Transport mechanisms and fate of microplastics in estuarine compartments: A review. (April 2022) - Malli, Ali; Corella-Puertas, Elena; Hajjar, Carla; Boulay, Anne-Marie
Abstract: Despite the importance of estuaries as transition zones between freshwater and marine compartments, their role in the transport of microplastics is still unclear. This review analyzes the findings pertaining to the transport mechanisms and other factors that influence the fate of microplastics in estuaries. It was found that the concentration of microplastics temporally varies under daily tides, monthly tides, and seasonal flows. Moreover, it spatially varies due to density effects, biofouling, aggregation, and salinity. Wind direction and intensity impact the spatiotemporal distribution of microplastics in the water column. Some of these processes transport microplastics to the estuarine sediments. Thereafter, microplastics are prone to resuspension by turbulence and bioturbation. Hence, estuaries act as temporary sinks that retain microplastics before being flushed to the ocean. Finally, a review of highly plastic-emitting rivers shows differences in the factors affecting the transport mechanisms of microplastics, which calls for regionalization when modelling their fate henceforward. Graphical abstract: Unlabelled Image Highlights: Estuaries are temporary sinks for microplastics before being emitted to the ocean. River flow has a higher effect on the transport of microplastics than tidal cycles. Turbulence and bioturbation resuspend microplastics from the surface sediments. Wind, biofouling, aggregation, and salinity affect the microplastic distribution. Regional data should be considered for modelling due to geographical differences.